Converting bimetallic M (M = Ni, Co, or Fe)–Sn nanoparticles into phosphides: a general strategy for the synthesis of ternary metal phosphide nanocrystals. Issue 7 (4th June 2019) - Düttmann, Anke; Bottke, Patrick; Plaggenborg, Thorsten; Gutsche, Christian; Parisi, Jürgen; Knipper, Martin; Kolny-Olesiak, Joanna
Abstract : Ternary metal tin phosphides are promising candidates for electrochemical or catalytic applications. Abstract : Ternary metal tin phosphides are promising candidates for electrochemical or catalytic applications. Nevertheless, their synthesis, neither as bulk nor nanomaterials is well investigated in the literature. Here, we describe a general synthetic strategy to convert bimetallic M–Sn (M = Ni, Co, and Fe) nanoparticles to ternary metal phosphides by decomposition of tributylphosphine at 300 °C. At high phosphorus concentrations, Ni3 Sn4 nanoparticles convert to hybrid structured Ni2 SnP and β-Sn. The CoSn2 and FeSn2 nanoparticles undergo a phosphorization, too and form hybrid nanocrystals reported here for the first time, containing ternary or binary phosphides. We identified the crystal structure of the nanoparticles via XRD and HRTEM measurements using the diffraction data given for Ni2 SnP in literature. We were able to locate the Ni2 SnP and β-Sn crystal structure within the nanoparticles to demonstrate the phase composition of the nanoparticles. By transferring the synthesis to cobalt and iron, we obtained nanoparticles exhibiting similar hybrid structures and ternary element compositions for Co–Sn–P and binary Fe–P and FeSn2 compositions. In the last step, we used the given information to propose a conversion mechanism from the binary M–Sn nanoparticles through phosphorization.